The Duovirate in Italian Municipia: Contribution to the Study of the Final Phase of the Municipalization Process in Central and Southern Italy - Sisani, Simone (Gerión. Revista de Historia Antigua, 2021)
The contribution analyzes systematically all known cases of municipia governed by duoviri within the Augustan regiones I-VII, aiming at offering a structural reading of the diffusion of municipal duovirate in the Italic area: the analysis allows to formulate hypothesis on the historical reasons for the institutional delay manifested by some areas of the peninsula, where the process of municipalization is fully accomplished only between the Caesarian and the Augustan ages.